The Application of Judicial Activism in the Constitutional Court Decision Number 90/PUU-XXI/2023 Regarding the Age Requirements for Presidential and Vice Presidential Candidates in Relation to the Theory of Legal Purpose - Abin Rifa Aldani; Ali Abdurrahman; Lailani Sungkar (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The Constitutional Court's decision 90/PUU-XXI/2023 has sparked controversy in society, as it is seen as exceeding its authority or encroaching on legislative powers, commonly referred to as open legal policy. The application of judicial activism in this decision has raised many questions, leading to polarization ahead of the 2024 Presidential Election. The aim of this research is to examine the application of judicial activism in the Constitutional Court's decision Number 90/PUU-XXI/2023 in relation to the theory of legal objectives. The methodology used in this study is normative legal methodology, utilizing various legal sources found in literature related to judicial activism in the Constitutional Court's decision 90/PUU-XXI/2023 regarding the age requirements for presidential and vice-presidential candidates, linked to the theory of legal objectives and the doctrine of legal activism, which are discussed and evaluated. The research findings indicate that the application of judicial activism in the Constitutional Court's decision Number 90/PUU-XXI/2023 is an inappropriate step that does not adequately consider the principle of virtue jurisprudence. Furthermore, the application of judicial activism in Decision 90/PUU-XXI/2023 does not fulfill the principles of legal objectives, which prioritize justice, followed by utility and certainty.